Perancangan Alat Pencetak Brown Sugar Cube - Menhendry Menhendry; Aan Ibadurrahman; Nurwahyu Aryo Anggono; Fardinal Fardinal; Haris Haris (Politeknik Negeri Padang, 2022)
Palm is a type of palm whose potential for high economic value and can thrive in Indonesia. Nagari Andaleh Baruh Bukik is an area in Tanah Datar District that is a center of palm crop production and has the potential to be developed by its economy. Seeing a promising market, the idea was born to process ant sugar into brown sugar cubes by making a brown sugar cube printer. The manufacture of brown sugar cubes using the manual press method with a pressing system utilizes the principle of the 2nd type of leverage, where the load point is between the power point and the fulcrum. This pressing system works if the lever is pulled by the operator according to the specified depth limit, to restore the position of the lever to its original position is to take advantage of the spring force. It takes about 392 N to press the mold. By doing the calculation so that a mechanical profit is obtained 3 times, the total force required to press is 130.6 N. The safety factor equation is 69.76 N/mm2 ≤ 200 MPa with the largest curved moment being 130.87 N/mm2, so this tool is safe and will not be bent. Power arm length: 34.5 cm, weight arm length: 11.5 cm. Designing components and assembling brown sugar cube printers using the SolidWork application.